Dinamika Relasi Suami Istri dalam Kesetaraan Gender pada Masyarakat Budaya Patriarki di Kepulauan Mandangin Kabupaten Sampang - Azizah, Rina Nur; Gaol, Indra Devian Lumban; Bisri, Mashur Hasan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
Gender is understood as an analytical framework that differentiates the roles of men and women. Patriarchal structures have historically reinforced gender inequality by placing men in control over women. The purpose of this study is based on the phenomenon of gender inequality in the Mandangin Islands, where women are often viewed as second-class. The method used in this study is a qualitative descriptive method. Observations were conducted in the Mandangin Islands and interviews were conducted with village government officials, community leaders, and the Mandangin Islands community. Data analysis techniques used were processing and preparing data for analysis, reading all data, starting with coding all data. From the results of the study, it can be concluded that the social structure in the Mandangin Islands, Sampang Regency, is still dominated by a patriarchal value system that limits women's space for movement. Local culture constructs the role of men as the sole authority holders, which indirectly creates unequal access to economic resources and education for women. Women are considered second-class, this encourages women to be actively involved in productive activities, such as processing seafood. Furthermore, the PEKA (Female Heads of Households) program, in the context of the Mandangin Islands community, has become a crucial turning point, exerting a powerful influence on the deeply rooted patriarchal culture. The research suggests that the government should expand the reach of the PEKA program as a community-based empowerment model integrated with regional policies (Perda) on women's protection. The government should involve religious and community leaders (village heads/heads) in dialogues on gender equality.